Intraosseous neurilemoma of the mandible with unusual multilocular presentation: a case report - Alves, Monica Ghislaine Oliveira; Rocha, Andre Caroli; Carvalho, Yasmin Rodarte [UNESP]; Almeida, Janete Dias [UNESP] (My University, 2021)
This case report describes an intraosseous neurilemoma, observed radiographically as a multilocular lesion, in a 12-year-old patient. Physical examination revealed facial asymmetry, swelling on the right side of the mandibular body, and bone expansion in the region of the base of the buccal sulcus. Panoramic radiography revealed a multilocular radiolucency on the right side of the mandibular body in the periapical region extending from the distal region of the first premolar root to the second molar and adjacent to the third molar. Evaluation of a radiograph obtained 3 years earlier for an orthodontic assessment revealed that the lesion was present, appearing as a unilocular radiolucency near the root of the mandibular right first molar. An incisional biopsy of the multilocular lesion was performed, and Antoni A and Antoni B histologic patterns were identified by microscopic analysis. Immunohistochemical analysis was conducted, and neoplastic cells stained positive for the S-100 protein. The patient underwent conservative surgical excision of the lesion, and no recurrence was observed during 7 years of clinical follow-up. Based on analysis of the present case and previous cases reported in the literature, intraosseous neurilemoma, especially its multilocular variant, is an uncommon neoplasm. In the present case, evaluation of the lesion when it was first radiographically detectable, prior to orthodontic treatment, would have permitted a more limited surgical approach for the excision of a small intraosseous lesion.
Keywords: mandible; neurilemoma; schwannoma